Effect of Treatment with Direct Acting Antiviral on Glycemic Control in Patients with Diabetes Mellitus and Chronic Hepatitis C - Jonathan G. Stine; Javelle A. Wynter; Blake Niccum; Virginia Kelly; Stephen H. Caldwell; Neeral L. Shah (Annals of Hepatology, 2017)
Introduction and aim. The effect of the new direct acting antiviral drugs (DAAs) for chronic hepatitis C (HCV) on glycemic control is unknown.Materials and methods. We conducted a retrospective cohort study of patients who were treated for chronic HCV with direct-acting antiviral medications at a single academic institution between May 2013 and April 2016. Univariate analysis was performed comparing subjects pre- and post-treatment.Results. One hundred seventy-five consecutive adult patients were treated for chronic HCV and met enrollment criteria. The majority (80.8%) were genotype 1 and overall cohort sustained virologic response at week 12 (SVR12) was 97.8%. Thirty-one (18.5%) had diabetes mellitus (DM); twenty-six had pre- and post-treatment HbA1c values. Of these, 76.9% were male and 61.5% had cirrhosis. Ninety-six percent were prescribed sofosbuvir-based therapy and all but one (96.8%) achieved SVR12. Three patients were started on treatment despite meeting the definition for poorly controlled DM (HbA1c > 9 mg/dL). There was no significant difference when comparing pre-treatment (7.36 mg/dL, 95% CI 6.55-8.16) to post-treatment HbA1c (7.11 mg/dL, 95% CI 6.34-7.88, p = 0.268). Thirty-one percent of subjects required dose escalation or the initiation of insulin based therapy during treatment.Discussion. Although chronic HCV is associated with exacerbation of insulin resistance, our results showed HbA1c to be unaffected by eradication of chronic HCV with DAA in diabetic patients with and without cirrhosis. Paradoxically, almost 1/3 of patients required escalation of anti-diabetic therapy during treatment. Long-term studies are warranted to understand the relationship between HCV viral eradication and insulin metabolism.